First Report of Corn Whorl Rot Caused by Serratia marcescens in China. Issue 11 (17th January 2015) - Wang, Xiao‐Qiang; Bi, Tao; Li, Xiang‐Dong; Zhang, Li‐Qun; Lu, Shi‐En
Abstract: Whorl rot is a novel disease of corn found in the Huang‐Huai‐Hai Plain, China. Common symptoms of the disease in fields include yellowing and water‐soaked brown necrosis of young leaves in the whorl of corn plants, which often results in rot of the whorl. Bacterial streaming was always observed from diseased samples. Bacterial isolates were obtained from symptomatic tissue and further confirmed to be the casual agent of the disease using Koch's Postulates. Sequence analysis of 16S rDNA, housekeeping gene groES‐groEL and BIOLOG tests revealed that the isolate B3R3 belongs to the bacterium Serratia marcescens . None of the corn cultivars evaluated showed acceptable resistance to the disease. To our knowledge, this is the first report on corn whorl rot caused by Serratia marcescens .